2020
DOI: 10.1002/cctc.202000858
|View full text |Cite|
|
Sign up to set email alerts
|

High Ethylene‐Yield Oxidative Dehydrogenation of Ethane Using Sulfur Vapor as a “Soft” Oxidant

Abstract: Ethylene remains one of the most valuable chemical feedstocks. Currently the industrial conversion of ethane to ethylene is achieved largely by steam cracking. The catalytic, highly exothermic oxidative dehydrogenation (ODH) of ethane with O2 is a challenging alternative that has been extensively studied on the laboratory scale. Here we investigate the possibility of using disulfur (S2) vapor as a thermodynamically “soft” oxidant for catalytically converting ethane to ethylene (“SODH”). Investigating a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…However, to our knowledge, this is the first time that O 2 and S 2 have been directly compared for a light alkane partial oxidation reaction. The results support the hypothesis introduced in prior literature that S 2 can afford higher olefin selectivity by moderating the thermodynamic driving force towards overoxidation [5a,6–7] …”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…However, to our knowledge, this is the first time that O 2 and S 2 have been directly compared for a light alkane partial oxidation reaction. The results support the hypothesis introduced in prior literature that S 2 can afford higher olefin selectivity by moderating the thermodynamic driving force towards overoxidation [5a,6–7] …”
Section: Figuresupporting
confidence: 90%
“…One approach to address this issue that has been explored in the ODHP literature is to replace O 2 with a softer oxidant, such as CO 2 or N 2 O, in order to mitigate the overoxidation to CO x. [4] In addition to oxygen‐containing molecules, this laboratory has previously shown that S 2 can be used as an alternative oxidant in a number of light alkane partial oxidations such as methane coupling to ethylene, [5] the ODH of ethane, [6] and ODHP [7] . For ODHP, we investigated a number of bulk metal sulfide surfaces as catalysts for this sulfur‐ODHP (SODHP) reaction, finding that the activation energy for propylene formation decreases with falling metal‐sulfur bond energy.…”
Section: Figurementioning
confidence: 99%
“…Catalytic runs begin by exposing the Fe 3 O 4 precatalyst to flowing H 2 S (sulfurization) for several hours to produce the active catalyst. Catalytic experiments flow Ar over molten S 8 (melting point = 388 K; boiling point = 718 K) to transport gaseous S 2 and a CH 4 into the reactor described previously (29,34,41,42). Gaseous products are quantified by gas chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the kinetic measurements were conducted below 865 °C. The apparent S 2 and methane rate orders were determined from the changes in methane conversion rate as a function of the S 2 and methane pressures, respectively (41,42). Note these empirical orders are overall apparent orders averaged over the various reaction network pathways (discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…11 Sulfur-containing gases represent another class of alternative oxidants. Previously, this laboratory showed that sulfur vapor, S 2 , can be utilized as an oxidant for various light alkane partial oxidations, including methane coupling, 15−17 ethane ODH, 18 and ODHP. 19,20 Unlike CO 2 −ODHP, SODHP remains exergonic at 500 °C.…”
Section: ■ Introductionmentioning
confidence: 99%